1994
DOI: 10.1016/0735-1097(94)90162-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecules in coronary artery disease

Abstract: To date, six families of cell adhesion molecules are known. These are cell surface receptors that mediate adhesion of cells to each other or to components of the extracellular matrix and include integrins, selectins, the immunoglobulin superfamily, cadherins, proteoglycans and mucins. These cell adhesion molecules play a key role in cell-cell interaction (such as among endothelium, monocytes, smooth muscle cells and platelets) and cell-extracellular matrix interaction (such as between leukocytes, platelets or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
203
0
12

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(219 citation statements)
references
References 92 publications
3
203
0
12
Order By: Relevance
“…24 On stimulation, P-selectin is rapidly translocated to the cell surface, where it mediates adhesion to carbohydrate ligand(s) on leukocytes. 25 P-selectin is involved in many acute inflammatory conditions mediated by neutrophils, 26,27 and because it regulates monocyte and T-lymphocyte emigration from the blood stream, 22,28 it may also be involved in chronic inflam- Ϫ/Ϫ P ϩ/ϩ mice (C) but not in lesions from apoE Ϫ/Ϫ P Ϫ/Ϫ mice (D). E and F, Sections were stained with oil red O, hematoxylin, and light green.…”
Section: Discussionmentioning
confidence: 99%
“…24 On stimulation, P-selectin is rapidly translocated to the cell surface, where it mediates adhesion to carbohydrate ligand(s) on leukocytes. 25 P-selectin is involved in many acute inflammatory conditions mediated by neutrophils, 26,27 and because it regulates monocyte and T-lymphocyte emigration from the blood stream, 22,28 it may also be involved in chronic inflam- Ϫ/Ϫ P ϩ/ϩ mice (C) but not in lesions from apoE Ϫ/Ϫ P Ϫ/Ϫ mice (D). E and F, Sections were stained with oil red O, hematoxylin, and light green.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and P-selectin that are synthesized and released from endothelial cells, as well as from other cells including fibroblasts, smooth muscle cells and platelets, E-selectin is produced specifically by endothelial cells (9). In this regard, E-selectin has been subject to several studies in terms of its relation to carotid atherosclerosis and the risk of coronary heart disease (10-13) given that higher likelihood of E-selection to be a specific marker for endothelial cell dysfunction and thereby the development of atherosclerosis than other adhesion molecules (14).…”
Section: Introductionmentioning
confidence: 99%
“…1 Cellular adhesion molecules (CAMs) are poorly expressed by the resting endothelium, but they are upregulated during atherogenesis. 2 Soluble forms of some CAMs can be found in plasma; it has been suggested that elevated plasma levels of some CAMs may be an index of endothelial activation 3 or even a molecular marker of early atherosclerosis. 4 Type 2 diabetes mellitus is associated with an increased risk of premature atherosclerosis, 5,6 and the circulating levels of some CAMs are higher in the diabetic patient.…”
mentioning
confidence: 99%